The Effect of BI-Rate, Net Interest Margin (NIM), and BOPO on Non-Performing Loans (NPL) in Conventional Banks Listed on the Indonesia Stock Exchange (IDX) in 2021-2024 - Putri Nur Asih Linggawati; Krisdiana (Indonesian Journal of Business Analytics, 2026)
This research seeks to examine how the BI Rate, NIM, and the BOPO shape the level of NPLs among conventional banks quoted on the IDX over the 2021–2024 window. Adopting a quantitative design, the analysis draws upon panel datasets compiled from published bank financial reports alongside relevant macroeconomic indicators. The sample was selected using purposive sampling in conventional foreign exchange banks. The analysis was carried out by regression of panel data using the REM model. The results showed that BI-Rate had a significant effect on NPLs in a negative direction, NIM had a significant effect on NPLs, while BOPO did not have a significant effect partially. Simultaneously, all three variables have a significant effect on NPLs. These findings confirm that banking credit risk is influenced by macro factors and the bank's internal performance.